2015
DOI: 10.1097/jcn.0000000000000270
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Relationship Quality on Health-Related Outcomes in Heart Failure Patients and Informal Family Caregivers

Abstract: Relationship quality and communication seem to matter in the health and well-being of both HF patients and their informal family caregivers. More research is needed to elucidate mechanisms and to design effective relationship-focused interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 45 publications
0
59
0
1
Order By: Relevance
“…Additionally, patients considering advanced therapies such as VADs and cardiac transplantation face additional anxieties as they anticipate or adjusting to a new life post-receipt. In addition to limitations in personal roles, patients experience wide variability in social support and the availability of informal caregivers (e.g., friends, spouses, children) (26,27). Regarding spirituality, patients with HF and poor health status report worse spiritual well-being compared to patients with metastatic lung and pancreatic cancer (28).…”
Section: Natural Opportunities To Integrate Palliative Domains In Hf mentioning
confidence: 99%
“…Additionally, patients considering advanced therapies such as VADs and cardiac transplantation face additional anxieties as they anticipate or adjusting to a new life post-receipt. In addition to limitations in personal roles, patients experience wide variability in social support and the availability of informal caregivers (e.g., friends, spouses, children) (26,27). Regarding spirituality, patients with HF and poor health status report worse spiritual well-being compared to patients with metastatic lung and pancreatic cancer (28).…”
Section: Natural Opportunities To Integrate Palliative Domains In Hf mentioning
confidence: 99%
“…Several reviews have evaluated particular aspects of HF family caregiving, including general experiences [12], relationship quality [13], needs [14], burden [15, 16], roles in patient self-care [1719] and left ventricular assist device management [20]. However, to our knowledge, the evidence-base of original research focused on HF family caregiving has yet to be assessed in its entirety in order to inform future research directions and priorities in HF palliative care.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, patient–carer dyads that had less satisfactory relationships to begin with may have had more trouble reaching consensus about CHF management roles and responsibilities after the diagnosis. Regardless of the direction of the association, other research has shown that better relationship quality has been associated with improved psychosocial and physical health outcomes among both members of the dyad across the CHF trajectory (Hooker, Grigsby, Riegel, & Bekelman, ). Thus, relationship quality generally, and dyadic congruence more specifically, should both be considered in future research investigating CHF outcomes.…”
Section: Discussionmentioning
confidence: 97%